2019
DOI: 10.1093/jnen/nlz090
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Not Tauopathy Is a Predominant Pathological Signature of Nodding Syndrome

Abstract: Nodding syndrome (NS) is an epileptic disorder occurring in children in African onchocerciasis endemic regions. Here, we describe the pathological changes in 9 individuals from northern Uganda who died with NS (n = 5) or other forms of onchocerciasis-associated epilepsy (OAE) (n = 4). Postmortem examinations were performed and clinical information was obtained. Formalin-fixed brain samples were stained by hematoxylin and eosin and immunohistochemistry was used to stain astrocytes (GFAP), macrophages (CD68), ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 32 publications
3
69
1
Order By: Relevance
“…Indeed, we carried out another post-mortem study in the same area, among five persons with NS and four persons with another type of OAE. This study revealed similar neuroinflammatory histopathological changes with mild to sparse deposits of tau-immunoreactive neurofibrillary tangles in 4/5 persons with NS and 2/4 persons with another form of OAE, suggesting that NS and other forms of OAE are caused by a similar phenomenon [38]. The tau deposits most likely are induced by repetitive seizures [39] with seizure-associated hypoxia [40] and possibly repeated head injuries [41].…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, we carried out another post-mortem study in the same area, among five persons with NS and four persons with another type of OAE. This study revealed similar neuroinflammatory histopathological changes with mild to sparse deposits of tau-immunoreactive neurofibrillary tangles in 4/5 persons with NS and 2/4 persons with another form of OAE, suggesting that NS and other forms of OAE are caused by a similar phenomenon [38]. The tau deposits most likely are induced by repetitive seizures [39] with seizure-associated hypoxia [40] and possibly repeated head injuries [41].…”
Section: Discussionsupporting
confidence: 56%
“…Nodding syndrome (NS) is a devastating childhood epilepsy, characterized by severe attacks of nodding of the head, progressive cognitive dysfunction, neurological deterioration, stunted growth and additional pathological neurological features [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The level O. volvulus microfilarial load in children was shown to be a predictor for developing OAE later in life [ 3 , 4 ]; however, the pathophysiological mechanism on how the O. volvulus parasite causes the seizures remains unknown. No parasites or O. volvulus DNA and no Wolbachia DNA (an O. volvulus endosymbiont) were found in cerebrospinal fluid [ 28 ] or in brain tissue of persons who had died of OAE [ 29 ]. An auto-immune mechanism induced by neurotoxic O. volvulus cross-reacting antibodies was proposed [ 30 ], but this hypothesis still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 99%